HUBUNGAN BBLR DAN ASI EKSLUSIF DENGAN KEJADIAN STUNTING DI PUSKESMAS LIMA PULUH PEKANBARU - Fitri, Lidia (Lembaga Layanan Pendidikan Tinggi (LLDIKTI) Wilayah X, 2018)
Stunting is one of the long-term indicators for malnutrition. Stunting prevalence in Indonesia about 37.2%. Babies born with low birth weight is 10.2% and the achievement of exclusive breastfeeding is 30.2%. Survey in Limapuluh Health Centre Pekanbaru, from 18 children who perform measurements, obtained 13 infants suffered stunting. The result of interviews showed that three of them were born with low birth weight (BBLR) and five are not given exclusive breastfeeding. This research is to find-out the correlation between low birth weight (BBLR) and exclusive breastfeeding with stunting in Limapuluh Health Centre Pekanbaru in 2017. Â This study was a quantitative analysis study used cross sectional strategy. Population consists of 300 people, sample consists of 75 people by accidental sampling technique. Analysis using univariat and bivariate. The result were 25 infant (33,3%) are stunting, 22 infant (29,3%) with low birth weight (BBLR) and Â not given exclusive breastfeeding are 55 infant (73,3%). There was a significant association between low birth weight (BBLR) with stunting was obtained p value 0.000 and association between exclusive breastfeeding with stunting was obtained p value 0.021 its mean p<0,05. There is a relationship between BBLR and exclusive breastfeeding with stunting events, the Ha accepted.Stunting merupakan salah satu indikasi buruknya status gizi pada anak. Prevalensi stunting di Indonesia sebesar 37,2%. Angka kejadian bayi dengan BBLR sebanyak 10,2% dan pencapaian ASI ekslusif 30,2%. Survey di Puskesmas Lima Puluh kota Pekanbaru Provinsi Riau didapatkan dari 18 orang balita yang di ukur, 13 orang diantaranya mengalami stunting. Hasil wawancara memperlihatkan bahwa 3 orang diantaranya lahir dengan BBLR dan 5 orang tidak diberikan ASI ekslusif. Tujuan penelitian untuk mengetahui hubungan berat badan lahir rendah (BBLR) dan ASI ekslusif dengan kejadian stunting di Puskesmas Lima Puluh Pekanbaru. Jenis penelitian analitik kuantitatif dengan desain cross sectional. Populasi berjumlah 300 orang balita, sampel 75 responden dengan teknik accidental sampling. Analisis data secara univariat dan bivariat. Hasil penelitian diperoleh sebanyak 25 orang (33,3%) balita mengalami stunting, balita dengan BBLR sebanyak 22 orang (29,3%) dan yang tidak diberikan ASI ekslusif sebanyak 55 orang (73,3%). Ada hubungan yang bermakna antara berat badan lahir rendah (BBLR) dengan kejadian stunting dimana p value 0.000 dan terdapat hubungan antara pemberian ASI ekslusif dengan kejadian stunting diperoleh nilai p value 0.021 artinya p<0,05. Dapat disimpulkan terdapat hubungan antara BBLR dan ASI eklusif dengan kejadian stunting, maka Ha diterima.